Synergistic effects of boron and saponin in mitigating salinity stress to enhance sweet potato growth - Younis, Uzma; Danish, Subhan; Datta, Rahul; Al Obaid, Sami; Ansari, Mohammad Javed (Scientific reports, 2024)
Salinity stress significantly hinders plant growth by disrupting osmotic balance and inhibiting nutrient uptake, leading to reduced biomass and stunted development. Using saponin (SAP) and boron (B) can effectively overcome this issue. Boron decreases salinity stress by stabilizing cell walls and membranes, regulating ion balance, activating antioxidant enzymes, and enhancing water uptake. SAP are bioactive compounds that have the potential to alleviate salinity stress by improving nutrient uptake, modulating plant hormone levels, promoting root growth, and stimulating antioxidant activity. That's why the current study was planned to use a combination of SAP and boron as amendments to mitigate salinity stress in sweet potatoes. Four levels of SAP (0%, 0.1%, 0.15%, and 0.20%) and B (control, 5, 10, and 20 mg/L B) were applied in 4 replications following a completely randomized design. Results illustrated that 0.15% SAP with 20 mg/L B caused significant enhancement in sweet potato vine length (13.12%), vine weight (12.86%), root weight (8.31%), over control under salinity stress. A significant improvement in sweet potato chlorophyll a (9.84%), chlorophyll b (20.20%), total chlorophyll (13.94%), photosynthetic rate (17.69%), transpiration rate (16.03%), and stomatal conductance (17.59%) contrast to control under salinity stress prove the effectiveness of 0.15% SAP + 20 mg/L B treatment. In conclusion, 0.15% SAP + 20 mg/L B is recommended to mitigate salinity stress in sweet potatoes.
Keywords: Boron; chlorofyl; solný stres; kořeny rostlin; Saponins; Salt Stress; saponiny; Salinity; bor; Plant Roots; Drug Synergism; Sweet potato; Saponin; Chlorophyll content; Photosynthesis; Photosynthetic rate; Ipomoea batatas; Antioxidant activity; synergismus léků; Chlorophyll; salinita; fotosyntéza